2021
DOI: 10.1038/s41388-021-01708-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of miR-200b/c in balancing EMT and proliferation revealed by an activity reporter

Abstract: Since their discovery, microRNAs (miRNAs) have been widely studied in almost every aspect of biology and medicine, leading to the identification of important gene regulation circuits and cellular mechanisms. However, investigations are generally focused on the analysis of their downstream targets and biological functions in overexpression and knockdown approaches, while miRNAs endogenous levels and activity remain poorly understood. Here, we used the cellular plasticity-regulating process of epithelial-to-mese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…After 2 weeks of survival (after all control pLKO-infected Cas9-A549 cells treated with the same KHS101 dose underwent complete cell death), the drug treatment was stopped to allow the selected cells to grow and be processed for the DNA preparation and the next-generation sequencing steps. The sequencing results on untreated cells indicated that it was possible to detect a total of 116,700 sgRNAs (all gRNAs excluding those with no counts) present in the library, with a 97% representation, a level similar to previous screenings [ 25 ], while in the treated group this percentage decreased to 56%, as a result of the drug selection. ‘Hits’ were ranked and gene ontology analysis on the 20 highest ranking ‘hits’ (Additional file 1 : Table S8) indicated that the genes whose knockout increased cellular resistance to KHS101 were mainly involved in regulating mitochondrial structure and activity (Fig.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…After 2 weeks of survival (after all control pLKO-infected Cas9-A549 cells treated with the same KHS101 dose underwent complete cell death), the drug treatment was stopped to allow the selected cells to grow and be processed for the DNA preparation and the next-generation sequencing steps. The sequencing results on untreated cells indicated that it was possible to detect a total of 116,700 sgRNAs (all gRNAs excluding those with no counts) present in the library, with a 97% representation, a level similar to previous screenings [ 25 ], while in the treated group this percentage decreased to 56%, as a result of the drug selection. ‘Hits’ were ranked and gene ontology analysis on the 20 highest ranking ‘hits’ (Additional file 1 : Table S8) indicated that the genes whose knockout increased cellular resistance to KHS101 were mainly involved in regulating mitochondrial structure and activity (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…Oxygen consumption rate (OCR) and extracellular acidification rate (ECAR) measurements were determined using the XFe96 Extracellular Flux Analyzer (Seahorse Bioscience/Agilent Technologies). Cells were seeded in specialized culture microplates at a density of 10,000–20,000 cells/well and prepared as describe in [ 25 ]. For Mito Stress Test (Agilent kit 103015–100) 1 μM oligomycin, 1 μM FCCP, 1 μM rotenone and 1 μM antimycin were sequentially injected at regular intervals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In turn, miR-200b directly represses expression of the HIF1A mRNA to form a HIF1A-ASCL2-miR-200 feedback loop that contributes to the ability of CRC cells to switch between EMT and MET [ 62 ]. Recent experiments that employed a miR-200b/c-sensitive fluorescent protein sensor reinforced the role for miR-200 in impeding EMT while promoting cell proliferation and implicated metabolic signaling in the control of miR-200b/c expression [ 64 ].…”
Section: Factors That Control Mir-200 Family Expression and Functionmentioning
confidence: 99%